New nonadiabatic pulsation computations on full PG 1159 evolutionary models: The theoretical GW Virginis instability strip revisited - Córsico, Alejandro Hugo (2006)
Aims. We reexamine the theoretical instability domain of pulsating PG 1159 stars (GW Vir variables). Methods. We performed an extensive g-mode stability analysis on PG 1159 evolutionary models with stellar masses ranging from 0.530 to 0.741 M⊙, for which the complete evolutionary stages of their progenitors from the ZAMS, through the thermally pulsing AGB and born-again phases to the domain of the PG 1159 stars have been considered. Results. We found that pulsations in PG 1159 stars are excited by the k-mechanism due to partial ionization of carbon and oxygen, and that no composition gradients are needed between the surface layers and the driving region, much in agreement with previous studies. We show, for the first time, the existence of a red edge of the instability strip at high luminosities. We found that all of the GW Vir stars lay within our theoretical instability strip. Our results suggest a qualitative good agreement between the observed and the predicted ranges of unstable periods of individual stars. Finally, we found that generally the seismic masses (derived from the period spacing) of GW Vir stars are somewhat different from the masses suggested by evolutionary tracks coupled with spectroscopy. Improvements in the evolution during the thermally pulsing AGB phase and/or during the core helium burning stage and early AGB could help to alleviate the persisting discrepancies.